After Brussels: understanding and countering ISIS's strategy. Issue 2 (7th February 2016) - Unknown
Abstract : The recent attacks in Brussels confirmed Islamic State's strategy of supplementing its flagging effort to establish a Middle East caliphate with an out-of-area campaign of urban terror focusing on Europe. Unity among Europe's policymakers remains key to securing the continent against terrorism and addressing the root causes of Muslim radicalisation.